012 Overnight light exposure acutely increases heart rate during sleep and decreases insulin sensitivity the following day. (3rd May 2021) - Grimaldi, Daniela; Reid, Kathryn; Mason, Ivy; Warlick, Chloe; Malkani, Roneil; Abbott, Sabra; Zee, Phyllis
Abstract: Introduction: Prior reports indicate that exposure to light at night negatively impacts sleep quality, autonomic and metabolic function, but the interaction between these physiologically interconnected systems is not fully elucidated. We examined the acute effects of nighttime light exposure on sleep macro and microarchitecture, heart rate (HR) and response to oral glucose tolerance test (OGTT), and the relationship between these measures. Methods: Twenty healthy adults (18 - 40 years) were randomized into Light or Dark groups and run in parallel for a three-day and two-night laboratory stay. The Light group (n=10) slept in the dark (< 3 lux) on Night 1 and slept with overhead room lights on (100 lux) on Night 2, while the Dark group (n=10) slept in the dark (< 3 lux) on both Nights 1 and 2. Overnight polysomnography (PSG) was used to assess sleep macro and microstructure (slow wave activity: SWA: 0.5–4 Hz, and slow oscillatory (SO) activity: 0.5–1 Hz), and beat-to-beat measurement of HR. A two-hour OGTT was completed each morning. The between groups change in PSG-derived measures and metabolic parameters from Night/Day 2 to Night/Day 1, was calculated. Results: While a greater percentage of time was spent in stage 2 (p= 0.003) and a smaller percentage of time was spent in stage 3 (p= 0.04), there were no between group differences in SWA and SO activity. Time series analysis of HR changes across the night from Night 1 to Night 2 showed higher HR in the Light vs the Dark group (p< 0.001). The change from Day 1 to Day 2 of the initial insulin response (60-min. area under the curve, AUC) showed a higher insulin response in the Light vs the Dark group (p= 0.029). The change in HR was positively correlated with the change in the 60-min. AUC of insulin (R= 0.46, p= 0.049). Conclusion: A single overnight light exposure acutely increases heart rate during sleep and decreases insulin sensitivity the following day and these responses appear to be associated, suggesting that elevated autonomic activity in response to light at night impacts next day metabolic responses. Support (if any): Center for Circadian and Sleep Medicine, UL1TR001422